ANALISA DIMENSI SALURAN DRAINASE UNTUK MENGATASI BANJIR DI JALAN BAY SALIM SEKIP JAYA KECAMATAN KEMUNING PALEMBANG - Bahri, Zainul; Setiawati, Mira; Alatif, M Rifki (Universitas Muhammadiyah Palembang, 2020)
Floods that occurred in Jalan Bay Salim, Sekip Jaya Village, Kemuning District, Palembang were caused by high rainfall with a long duration, inadequate drainage canals filled with rubbish, sediment deposits that were thick enough and cross section of drainage channels that could no longer hold water in large quantities so that there is an overflow of water from the drainage channel.The dimensions of the drainage channel in Jalan Bay Salim Sekip Jaya, Kemuning District in Palembang, there can be two rectangular channels, as follows: First channel: H = 1 m, b = 2 m, y = 0.61 m, p = 200 m, by being able to accommodate discharge: 1,376 m3 / sec, with maximum discharge: 0,365 m3 / sec, second channel: H = 0.6, b = 0.5m, y = 0.3m, p = 200m, by being able to accommodate discharge: 0,7584 m3 / sec, with maximum discharge: 0,779 m3 / sec. So from the observation only the first channel can accommodate maximum flowrate.Based on the results of the analysis that the second channel is no longer able to accommodate the maximum discharge, therefore in order to accommodate the maximum discharge it is necessary to analyze the dimensions of the channel that can accommodate the maximum discharge by normalizing by changing the dimensions of the channel as follows: second channel: H = 0.6, b = 1 m, y = 0.5 m, p = 200 m, so it can hold the discharge: 2,075m3 / sec, with a maximum discharge of 0,779 m3 / sec.